Implementasi Green Accounting di RSUD Bendan Kota Pekalongan - Rika Adriyana; Dina Amalia Mahmudah; Anggrainy Putri Ayuningrum (Pena: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
Green accounting provides an overview of protecting the environment by combining environmental benefits with environmental costs such as waste management. The purpose of this study is to find out how the implementation of green accounting in Bendan Hospital and how the accounting treatment starts from identifying, recognizing, measuring, presenting, and disclosing the costs of waste management applied at Bendan Hospital. The method used in this research is a qualitative approach. The object of research is Bendan Hospital, Pekalongan City. The results of this study indicate (1) Bendan Hospital has identified the costs incurred for waste management but have not been identified specifically. (2) Recognition of each cost incurred for waste management using the accrual basic method. (3) Measurement of waste management costs in monetary units, namely rupiah multiplied by waste per kilogram. (4) Bendan Hospital presents these costs in the budget realization report and operational report. (5) Bendan Hospital has not reported environmental costs related to waste management specifically.